PENGARUH BUDAYA ORGANISASI DAN ETOS KERJA TERHADAP KUALITAS PELAYANAN MAHASISWA - Yunita Indriany (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
The influence of organizational culture and work ethos against the quality of student services (LP3I Polytechnic Case Study in Jakarta, Campus Cibinong) This study aims to how much influence organizational culture, work ethic on the level of customer satisfaction. The sampling method used is Proportionate random sampling. The sample in this study follows the formula of Slovin, or as many as 80 students and 21 staff employees. The data that have met the test of validity and reliability testing further processed to generate a regression equation of Y = X1 + 0.025 0.457+ 0678 X2, where Y is the variable quality of student services, organizational culture is a variable X1 and X2 are variables work ethic. Hypothesis testing using t-test showed that each of the independent variables studied was shown to significantly affect the dependent variable partially on the quality of student services. Then through the F test can be seen that the two independent variables were examined simultaneously shown to affect the dependent variable quality of student services. Figures Adjusted R Square of 0.697menunjukkan that 69.7% Customer Satisfaction variables can be explained by the two independent variables, while the remaining 30.3% is explained by other variables.